Midwives' use of best available evidence in practice: An integrative review - De Leo, Annemarie (J Clin Nurs, 2019)
AIMS AND OBJECTIVES: To synthesise international research that relates to midwives' use of best available evidence in practice settings and identify key issues relating to the translation of latest evidence into everyday maternity care. BACKGROUND: Midwifery is a research‐informed profession. However, a gap persists in the translation of best available evidence into practice settings, compromising gold standard maternity care and delaying the translation of new knowledge into everyday practice. DESIGN: A five‐step integrative review approach, based on a series of articles published by the Joanna Briggs Institute (JBI) for conducting systematic reviews, was used to facilitate development of a search strategy, selection criteria and quality appraisal process, and the extraction and synthesis of data to inform an integrative review. METHODS: The databases CINAHL, MEDLINE, Web of Science, Implementation Science Journal and Scopus were searched for relevant articles. The screening and quality appraisal process complied with the PRISMA 2009 checklist. Narrative analysis was used to develop sub‐categories and dimensions from the data, which were then synthesised to form two major categories that together answer the review question. RESULTS: The six articles reviewed report on midwives' use of best available evidence in Australia, the UK and Asia. Two major categories emerged that confirm that although midwifery values evidence‐based practice (EBP), evidence‐informed maternity care is not always employed in clinical settings. Additionally, closure of the evidence‐to‐practice gap in maternity care requires a multidimensional approach. CONCLUSION: Collaborative partnerships between midwives and researchers are necessary to initiate strategies that support midwives' efforts to facilitate the timely movement of best available evidence into practice. RELEVANCE TO CLINICAL PRACTICE: Understanding midwives' use of best available evidence in practice will direct future efforts towards the development of mechanisms that facilitate the timely uptake of latest evidence by all maternity care providers working in clinical settings.